Reaching the missing middle: Overcoming hunger and malnutrition in middle income countries - Fan, Shenggen; Cousin, Ertharin (International Food Policy Research Institute, 2015)
Eliminating hunger and malnutrition around the globe cannot be achieved without a new approach to dealing with the problem in middle income countries. Here’s why this is so, how the middle income countries should respond, and what the international community can do to help.